Aesopic conversations : popular tradition, cultural dialogue, and the invention of Greek prose - Kurke, Leslie (Princeton, N.J. ; Oxford : Princeton University Press, 2011)
Examining the figure of Aesop and the traditions surrounding him, Aesopic Conversations offers a portrait of what Greek popular culture might have looked like in the ancient world. What has survived from the literary record of antiquity is almost entirely the product of an elite of birth, wealth, and education, limiting our access to a fuller range of voices from the ancient past. This book, however, explores the anonymous Life of Aesop and offers a different set of perspectives. Leslie Kurke argues that the traditions surrounding this strange text, when read with and against the works of Greek high culture, allow us to reconstruct an ongoing conversation of "great" and "little" traditions spanning centuries. Evidence going back to the fifth century BCE suggests that Aesop participated in the practices of nonphilosophical wisdom (sophia) while challenging it from below, and Kurke traces Aesop's double relation to this wisdom tradition. She also looks at the hidden influence of Aesop in early Greek mimetic or narrative prose writings, focusing particularly on the Socratic dialogues of Plato and the Histories of Herodotus. Challenging conventional accounts of the invention of Greek prose and recognizing the problematic sociopolitics of humble prose fable, Kurke provides a new approach to the beginnings of prose narrative and what would ultimately become the novel. Delving into Aesop, his adventures, and his crafting of fables, Aesopic Conversations shows how this low, noncanonical figure was -- unexpectedly -- central to the construction of ancient Greek literature. --
Introduction: an elusive quarry: In search of ancient Greek popular culture; Explaining the joke: a roadmap for classicists; Synopsis of method and structure of argument -- Aesop and the contestation of Delphic authority: Ideological tensions at Delphi; the Aesopic critique; Neoptolemus and Aesop: sacrifice, hero cult, and competitive scapegoating -- Sophia before/beyond philosophy: the tradition of Sophia; Sophists and (as) sages; Aristotle and the transformation of Sophia -- Aesop as sage: political counsel and discursive practice; Aesop among the sages; Political animals: fable and the scene of advising -- Reading the life: the progress of a sage and the anthropology of Sophia: an Aesopic anthropology of wisdom; Aesop and Ahiqar; Delphic theoria and the death of a sage; the bricoleur as culture hero, or the art of extorting self-incrimination -- The Aesopic parody of high wisdom: demystifying Sophia: Hesiod, Theognis, and the seven sages; Aesopic parody in the visual tradition? -- Aesop at the invention of philosophy: the problematic sociopolitics of mimetic prose; Mimesis and the invention of philosophy; the generic affiliations of Sokratikoi logoi -- The battle over prose: fable in sophistic education and Xenophon's Memorabilia: Sophistic fables; traditional fable narration in Xenophon's Memorabilia -- Sophistic fable in Plato: parody, appropriation, and transcendence: Plato's Protagoras: debunking Sophistic fable; Plato's symposium: ringing the changes on fable -- Aesop in Plato's Sokratikoi logoi: analogy, elenchos, and disavowal: Sophia into philosophy: Socrates between the sages and Aesop; the Aesopic bricoleur and the "old Socratic tool-box"; sympotic wisdom, comedy, and Aesopic competition in Hippias major -- Historie and logopoiia: two sides of Herodotean prose: history before prose, prose before history; Aesop ho logopoios; Plutarch reading Herodotus: Aesop, ruptures of decorum, and the non-Greek -- Herodotus and Aesop: some soundings : Cyrus tells a fable; Greece and (as) fable, or resignifying the hierarchy of genre; fable as history; the Aesopic contract of the histories: Herodotus teaches his readers.
Includes bibliographical references (pages 433-461) and indexes.
Print version record.
JSTOR
Keywords: Aesop's fables; Aesop -- Influence; Aesop -- Influence; Aesop; Aesop's fables; Greek prose literature -- History and criticism; Fables, Greek -- History and criticism; Popular culture -- Greece -- History -- To 146 B.C.; Popular culture and literature -- Greece -- History -- To 146 B.C.; Literary form -- History -- To 1500.; Literature and society -- Greece -- History -- To 146 B.C.; Greece, Ancient; Prose grecque -- Histoire et critique; Fables grecques -- Histoire et critique; LITERARY CRITICISM -- Ancient & Classical; HISTORY -- Ancient -- Greece; Fables, Greek; Greek prose literature; Influence (Literary, artistic, etc.); Literary form; Literature and society; Popular culture; Popular culture and literature; Greece; To 1500; Criticism, interpretation, etc; History